2019
DOI: 10.22215/sdhlab/2019.4
|View full text |Cite
|
Sign up to set email alerts
|

• Report: Interventions for Rural and Remote Youth Mental Health

Abstract: What is known? • Rural and remote communities in Australia and Canada have high burden of youth mental illness • Interventions for youth mental health in these communities is varied and insufficient What does this study add? • Barriers and facilitators of rural and remote youth mental health interventions are examined within the context of the Social Ecology Model • Future directions for rural and remote mental health interventions informed by the Social Ecology Model are explored Report: Interventions for rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…While emotionally engaging YP is important, it is not enough. Corroborating with existing literature, the present study found that YP wanted to feel a sense of empowerment and active participation in the process of learning about and managing their mental health, and seeking help [10,45,46]. This sample of YP asked to be equipped with more confidence and skills around talking about and managing their mental health.…”
Section: Empowermentsupporting
confidence: 64%
See 3 more Smart Citations
“…While emotionally engaging YP is important, it is not enough. Corroborating with existing literature, the present study found that YP wanted to feel a sense of empowerment and active participation in the process of learning about and managing their mental health, and seeking help [10,45,46]. This sample of YP asked to be equipped with more confidence and skills around talking about and managing their mental health.…”
Section: Empowermentsupporting
confidence: 64%
“…YP for example connected better with counsellors who "understood drought" [15] or who had experienced bushfires. Following this rationale, it seems advantageous to deliver locally tailored mental health education and support by professionals who are familiar with the culture and needs of individual communities [10,24]. Further research into the importance of this aspect is indicated.…”
Section: Engagementmentioning
confidence: 99%
See 2 more Smart Citations